The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1109/22.841963
|View full text |Cite
|
Sign up to set email alerts
|

Spectral transmittance of lossy printed resonant-grid terahertz bandpass filters

Abstract: In this paper, we present terahertz bandpass filters composed of resonant arrays of crossed slots in lossy metal films deposited on dielectric membranes. The filters exhibit insertion loss as low as 1.9 dB at room temperature and 1.2 dB at 77 K at a center frequency of 2.2 THz. It is found that the dielectric substrate introduces a downward shift in frequency not predicted by standard mean dielectric-constant approximations. This shift is proportional to the permittivity and thickness of the substrate, and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 11 publications
2
44
0
Order By: Relevance
“…were previously highlighted by other authors for composite materials operating in the Terahertz range [16][17][18][19], in agreement with the static surface resistance variation…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…were previously highlighted by other authors for composite materials operating in the Terahertz range [16][17][18][19], in agreement with the static surface resistance variation…”
Section: Discussionsupporting
confidence: 89%
“…Even if the trend of the attenuation clearly depends on metal thickness (see Figure 6), the introduction of this surface resistance values in the MoM code produces a smaller attenuation with respect to the measured one. In the referred work [16][17][18][19], the authors found the same attenuation behaviour but they computed higher static surface resistance values because of a thinner substrates. According to [5,20], the blueshift is qualitatively associated to a dipole-dipole interaction, which is increasing important in our samples as the thickness allows the circulation of currents in the transverse direction.…”
Section: Discussionmentioning
confidence: 69%
“…Different FSS configurations have been proposed for this kind of application: free-standing perforated metal foils [4], perforated grids supported by a membrane [5], symmetric hybrid radomes (perforated grids sandwiched between two identical dielectric layers) [6], Ch. 7, and multilayer free-standing slot arrays [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…A simple theoretical model is presented and shows good agreement with the experimental data. Although the microwave and terahertz transmission through thin-metal films or metal foils perforated periodically with apertures has been studied since 1967 [1][2][3][4][5][6], unusual high-transmission resonances through subwavelength hole arrays were only recently discovered [7,8] at optical frequencies. These resonances occurred at wavelengths different from those predicted by the classic diffraction theory [2].…”
mentioning
confidence: 99%